The Contribution of Memorizing the Qur'an to the Arabic Vocabulary Mastery of Students Rumah Tahfizh Baeturrahman - Umam, Ahmad Zaimul; Ridlo, Akhmad; Syihabuddin, Syihabuddin; Nurbayan, ayan (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2024)
The Qur'an and Arabic language are inseparable from one another. Learning the Qur'an also means learning Arabic, and vice versa. This study aims to describe the contribution of memorizing the Qur'an carried out by students at Baeturrahman Tahfizh House to the mastery of Arabic vocabulary. This research uses qualitative research methods. The data collection technique used observation, interview and documentation techniques. The results of this study indicate that the contribution of memorizing the Qur'an owned by underage students of the Baeturrahman Tahfizh House to the mastery of Arabic vocabulary has only been achieved in the aspect of mastery of pronunciation, while in the aspects of meaning, istiqaq, and usage, they have not been able to master it because of their limited ability conditions.